2016
DOI: 10.1111/myc.12517
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring and safety of intravenous voriconazole formulated with sulfobutylether β‐cyclodextrin in haematological patients with renal impairment

Abstract: SummaryBecause of concerns about accumulation of cyclodextrin, oral voriconazole is recommended for patients with renal impairment. However, intravenous voriconazole may occasionally be imperative in critically ill patients with life-threatening invasive aspergillosis. We investigated the clinical effects of intravenous voriconazole formulated with sulfobutylether b-cyclodextrin (SBECD) in patients with renal impairment. A prospective observational study was conducted on 25 adult patients with haematological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
1
12
1
2
Order By: Relevance
“…Three months after intravenous VRC treatment, the median serum creatinine level was 0.80 mg/dl (range, 0.36 to 1.50 mg/dl) in 81 evaluable patients, and no patient required renal replacement therapy. Previous studies showed that use of intravenous VRC was not associated with renal dysfunction in patients with baseline moderate to severe renal impairment in several different clinical contexts (3)(4)(5)(6)(7)(8). However, the median duration of intravenous VRC treatment in the previous studies was much shorter than that in our study (3)(4)(5)(6)(7).…”
contrasting
confidence: 72%
See 2 more Smart Citations
“…Three months after intravenous VRC treatment, the median serum creatinine level was 0.80 mg/dl (range, 0.36 to 1.50 mg/dl) in 81 evaluable patients, and no patient required renal replacement therapy. Previous studies showed that use of intravenous VRC was not associated with renal dysfunction in patients with baseline moderate to severe renal impairment in several different clinical contexts (3)(4)(5)(6)(7)(8). However, the median duration of intravenous VRC treatment in the previous studies was much shorter than that in our study (3)(4)(5)(6)(7).…”
contrasting
confidence: 72%
“…Previous studies showed that use of intravenous VRC was not associated with renal dysfunction in patients with baseline moderate to severe renal impairment in several different clinical contexts (3)(4)(5)(6)(7)(8). However, the median duration of intravenous VRC treatment in the previous studies was much shorter than that in our study (3)(4)(5)(6)(7). Indeed, intravenous SEBCD administered at Ն160 mg/kg causes dose-dependent changes in renal tubular vacuolation in animal models treated for 1 to 6 months (1), but there are no data evaluating the effect of cumulative doses of SBECD on renal function in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the experience with voriconazole, also containing sulfobutylether-β-cyclodextrin, we have learned that the benefits of efficacious treatment may outweigh the risk associated with accumulation of sulfobutylether-βcyclodextrin. In addition, sulfobutylether-β-cyclodextrin appeared to accumulate by about sixfold in the kidney, but was not nephrotoxic itself [123][124][125]. Data on pharmacokinetics, efficacy, and safety upon long-term posaconazole use are lacking in this special population, for which future studies are expected to fill the gap.…”
Section: Patients With Hepatic or Renal Impairmentmentioning
confidence: 98%
“…La característica lipofílica de los azoles, hace que sea necesario combinarlos con moléculas como la ciclodextrina, que se convierte en el vehículo de transporte del fármaco; se ha demostrado que este compuesto en pacientes con enfermedad renal y tasa de filtración glomerular menor a 50 ml/min/1,73 m 2 , se acumula, precipitando la ocurrencia de más efectos adversos relacionados con la nefrotoxicidad; sin embargo, su impacto clínico sigue sin estar claro. Es así como en pacientes adultos con enfermedad renal crónica y neoplasias hematológicas, a quienes se administró voriconazol endovenoso para el tratamiento de AI, no se encontró deterioro de la función renal ni efectos adversos graves 27 .…”
Section: Farmacocinética Y Farmacodinamiaunclassified